Effect of kinematic hardening parameters on fatigue crack growth. (April 2020) - Borges, M.F.; Antunes, F.V.; Prates, P.A.; Branco, R.; Cruces, A.S.; Lopez-Crespo, P.
Highlights: The effect of kinematic parameters on FCG was predicted numerically using the plastic CTOD. Increasing kinematic parameters reduces non-linearly fatigue crack growth. The kinematic parameters have a limited effect on crack closure. The effect of kinematic saturation stress, XSat, is more relevant than the effect of kinematic saturation rate, CX . Abstract: The parametric study of the effect of material properties on fatigue crack growth (FCG) rarely has been addressed in literature. The consideration of plastic CTOD as crack driving force opened the opportunity to predict FCG rate numerically and therefore to develop parametric studies focused on the effect of loading, geometrical and material parameters. The objective here is to study the effect of kinematic saturation stress, XSat, and kinematic saturation rate, CX, on FCG using this numerical approach. The increase of the kinematic parameters reduced the plastic CTOD and therefore the FCG rate. The variation is non-linear and the rate of variation of δp decreases with the increase of XSat and CX . The effect of the kinematic saturation stress, XSat, is more relevant than the effect of kinematic saturation rate, CX . On the other hand, a small effect of kinematic hardening parameters on crack closure was found. Finally, the increase of the number of load cycles between crack increments produced a great reduction of crack closure but no effect of plastic CTOD on models without contact of crack flanks.